Sosialisasi Peran Imam Sutan Dalam Pengembangan Budaya Dan Agama Islam Di Kampung Hinai Kabupaten Langkat - Rezky Dwinda Br Silalahi; Khofifah Riana Br Bangun; M. Fadeli Riansyah; Sufriansyah; Nurul Hasanah (peduli riset dan pengabdian masyarakat, 2025)
The Role of Imam Sutan in the Development of Islamic Culture and Religion in Hinai Village, In the context of a diverse society, Imam Sutan not only functions as a spiritual leader but also as an agent of social change. This study uses a qualitative approach with interview methods and participatory observation to collect data. The results of the study indicate that Imam Sutan has several important roles: as an educator, mediator, and preserver of tradition. As an educator, he teaches Islamic values ​​to the younger generation through teachings in the mosque and social activities. As a mediator, he plays a role in resolving conflicts in the community, maintaining harmony between residents, and strengthening community solidarity. In addition, Imam Sutan also plays a role in preserving local traditions that are in line with Islamic teachings, thus creating synergy between local culture and religious values. Through various religious and social activities, Imam Sutan has succeeded in integrating Islamic principles into the daily lives of the community, which has a positive impact on strengthening the cultural and spiritual identity of the Hinai Village community. This study is expected to contribute to the understanding of the role of religious leaders in the context of local culture, as well as encourage further research on the dynamics of interaction between religion and culture.